Impulse Response Modeling of Underwater Optical Scattering Channels for Wireless Communication - Ruben Boluda-Ruiz; Pedro Rico-Pinazo; Beatriz Castillo-Vazquez; Antonio Garcia-Zambrana; Khalid Qaraqe (IEEE Photonics Journal, 2020)
Despite the fact that underwater optical wireless communication (UOWC) systems are able to provide high-data rate links with high security, the performance of these systems presents several limitations related to the maximum achievable distance due to attenuation, and scattering effects. Hence, quantifying the signal attenuation, and the time-dispersion produced by such effects represents a crucial work in channel modeling. Motivated by this, we present, for the first time, a novel, and unified impulse response modeling of underwater optical scattering channels based on the superposition of one impulsive component, and one dispersive component with two degrees of freedom. We provide analytical results for channel path loss, and channel impulse response (CIR) which are validated through Monte-Carlo simulations based on photon-tracing for clear ocean, coastal, and harbor waters. In order to provide a physical insight, the developed CIR is used to compute the root-mean-square (RMS) delay spread as a function of distance, and type of water, as well as to analyze in greater detail the impact of inter-symbol interference (ISI) on the data rate. These outcomes can be used for high-speed systems design, and optimization.